Gas temperature measurement in the active zone of streamer discharge under different applied voltages - Bolotov, O.V.; Golota, V.I.; Taran, G.V. (Вопросы атомной науки и техники, 2021)
The experimental results on the gas temperature measurement in the active zone of streamer discharge in air at the atmospheric pressure are presented. The gas temperature value was obtained by the optical method for measuring the relative intensity of the rotational lines for the radiation of the second positive (II⁺) system of molecular nitrogen, transition bands (C₃ПU(0) →B-₃Пg(0)). It was found that in discharge gap d = 8 mm, depending on the applied voltage (in the range of 6.1…7.8 kV with a step of 0.2 kV), the gas temperature varied from 609 to 739 K. The unevenness of the gas temperature change in the active zone of discharge with the increase in the applied voltage is shown. This may be related to the possible changes in the rotational state of nitrogen molecules upon excitation of their electronic state by electrons.